Nitrogen removal performance and bacterial community analysis of a multistage step-feeding tidal flow constructed wetland - Khajah, Mishari; Bydalek, Franciszek; Babatunde, Akintunde O.; Al-Matouq, Abdullah; Wenk, Jannis; Webster, Gordon (Frontiers in Water, 2023)
A multistage mesocosm vertical flow constructed wetland system was designed to treat synthetic domestic wastewater with a high nitrogen (N) load. The study aim was to determine the impact of design and operational variables on N removal efficiency in such systems. A tidal flow operational strategy enhanced aeration and was coupled with a step-feeding approach to promote N removal. Over the 420-day running period N removal rates were between 70 and 77 gN/m³/d, for a step-feeding ratio range of 60:40 to 80:20. The system was able to remove 91-95% of chemical oxygen demand, 74-91% of ammonium-N and 66-81% of total-N. Tidal flow and step-feeding strategies significantly impacted nitrogen removal with the best performance at a step-feeding ratio of 80:20 providing a carbon to nitrogen (C/N) ratio of 4-5. The bacterial diversity increased at each stage throughout the system with dominating phyla Proteobacteria, Firmicutes, Planctomycetes, Bacteroidetes, Chloroflexi, Verrucomicrobia and Acidobacteria. Dominant bacteria at the genus level were Thiothrix, Planctomyces, Azonexus, Pseudoxanthomonas, Hydrogenophaga, Gemmobacter and other genera suggesting that N removal was accomplished via diverse metabolic pathways, including autotrophic nitrification, heterotrophic denitrification, autotrophic denitrification, and ANAMMOX. This study shows benefits of step-feeding strategies in tidal flow constructed wetlands as a cost-effective solution for minimizing external carbon input to achieve effective N removal.